Single and sequential applications of metconazole alone or in mixture with pyraclostrobin to improve Fusarium head blight control and wheat yield in Brazil - Spolti,Piérri (2013)
Four fungicide trials were conducted in northern RS state during 2009. Six treatments, from the combination of one (flowering = F) or two applications (F + 10 days) of metconazole sprayed alone or in mixture with pyraclostrobin were tested. Fusarium head blight incidence (INC) and severity (SEV) were assessed at the pre-harvest period and Fusarium-damaged kernel (FDK), kernel infection (KI) and deoxynivalenol (DON) and nivalenol (NIV) trichothecenes were quantified on harvested kernels. Disease incidence ranged from 43.8% to 90% and from 7.3% to 31% respectively in the unsprayed check. Both INC and SEV were reduced in all fungicide treatments compared to the check across trials. Levels of FDK and KI were not affected by fungicides where susceptible and moderately resistant cultivars were used, respectively. The fungicide x cultivar susceptibility interaction was significant with the highest severity reduction (>70%) susceptible cultivars. Overall yield increased (+400 kg/ha) in fungicide-treated plots compared to the check; the mixture of fungicides led to higher increase (+275kg/ha) in yield. Yield increased modestly (+150 kg/ha) for two sprays compared to a single spray. Both DON and NIV were found in variable levels across trials but non significant effect of fungicides was found on mycotoxin levels.